SCIENTIFIC REVIEW OF PRODUCTION ON VIOLENCE IN THE CONTEXT OF PUBLIC HEALTH (Fiep Bulletin - online, 2013)
Violence as a public health problem is reflected in all spheres in the daily lives of people. It is therefore important to consider is how it is being seen and treated in the health sector. In this sense, it is essential to the study on this topic identifying and analyzing the existence of scientific articles on violence in the reality of public health. This is a literature search, whose goal is to characterize the scientific production on violence in the context of public health published in the period 2004 to August 2008, in the databases of Mental Health / Regional Library of Medicine (BVS / BIREME), as the year of publication, type of study, method, manner of publication, language and theme of the study. We found 45 of these works and 42 were selected. Of this total (42), 14 (33.3%) was published in 2006; 25 (59.5%) used the kind of descriptive study as the most appropriate to find the theme of violence; 23 (54.8% ) of publications were produced with a qualitative approach, and the manner of publication, both abstract as full text was also available, 21 (50.0%) each; 33 (78.6%) were available in English and the thematic more published, 12 (28.6%) work searched urban violence as the object of his study. Deemed to be a lack of work that deal with the violence in the context of public health, therefore, the priority is to continue to carry out research on those topics and at the same time, investing in the development of research directed to those hitherto little studied.
Keywords: Violence; Public Health; Publications